Viscoelastic Properties of Contemporary Bulk-Fill Restoratives: A Dynamic-Mechanical Analysis - Ong, Joshua E-Xin; Yap, Adrian U-Jin; Hong, Ja Young; Eweis, Ahmed Hesham; Yahya, Noor Azlin (Academy of Operative Dentistry, 2018)
This study investigated the viscoelastic properties of contemporary bulk-fill restoratives in distilled water and artificial saliva using dynamic mechanical analysis. The materials evaluated included a conventional composite (Filtek Z350), two bulk-fill composites (Filtek Bulk-fill and Tetric N Ceram), a bulk-fill giomer (Beautifil-Bulk Restorative), and two novel reinforced glass ionomer cements (Zirconomer [ZR] and Equia Forte [EQ]). The glass ionomer materials were also assessed with and without resin coating (Equia Forte Coat). Test specimens 12 × 2 × 2 mm of the various materials were fabricated using customized stainlesssteel molds. After light polymerization/initial set, the specimens were removed from the molds, finished, measured, and conditioned in distilled water or artificial saliva at 37°C for seven days. The materials (n=10) were then subjected to dynamic mechanical testing in flexure mode at 37°C and a frequency of 0.1 to 10 Hz. Storage modulus, loss modulus, and loss tangent data were subjected to normality testing and statistical analysis using one-way analysis of variance/Dunnett's test and t-Test at a significance level of p < 0.05. Mean storage modulus ranged from 3.16 ± 0.25 to 8.98 ± 0.44 GPa, while mean loss modulus ranged from 0.24 ± 0.03 to 0.65 ± 0.12 GPa for distilled water and artificial saliva. Values for loss tangent ranged from 45.7 ± 7.33 to 134.2 ± 12.36 (10 -3 ). Significant differences in storage/ loss modulus and loss tangent were observed between the various bulk-fill restoratives and two conditioning mediums. Storage modulus was significantly improved when EQ and ZR was not coated with resin.